EFSUMB Guidelines on Interventional Ultrasound (INVUS), Part III – Abdominal Treatment Procedures (Long Version) - Dietrich, C. F.; Lorentzen, T.; Appelbaum, L.; Buscarini, E.; Cantisani, V.; Correas, J. M.; Cui, X. W.; D’Onofrio, M.; Gilja, O. H.; Hocke, M.; Ignee, A.; Jenssen, C.; Kabaalioğlu, A.; Leen, E.; Nicolau, C.; Nolsøe, C. P.; Radzina, M.; Serra, C.; Sidhu, P. S.; Sparchez, Z.; Piscaglia, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
The third part of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) Guidelines on Interventional Ultrasound (INVUS) assesses the evidence for ultrasound-guided and assisted interventions in abdominal treatment procedures. Recommendations for clinical practice are presented covering indications, contraindications, and safe and effective performance of the broad variety of these techniques. In particular, drainage of abscesses and fluid collections, interventional tumor ablation techniques, interventional treatment of symptomatic cysts and echinococcosis, percutaneous transhepatic cholangiography and drainage, percutaneous gastrostomy, urinary bladder drainage, and nephrostomy are addressed (long version).
Keywords: guideline; ultrasound guidance; abscess; hepatocellular carcinoma; liver metastases; cysts; radio frequency ablation; drainage; safety